KOMPETENSI PROGRAM STUDI DIPLOMA TEKNIK PERKAPALAN DALAM INDUSTRI MARITIM INDONESIA - Mohd Ridwan; Eko Yulianto (Gema Teknologi, 2010)
Mohd Ridwan, Eko Yulianto, in paper competency of naval architecture diploma program on Indonesian maritime industry explain that Shipbuilding engineering professionals is part of the leading maritime industry is expected to become the motor of development of national maritime fleet in the implementation of cabotage (Impres No.5, 2005), this will reduce foreign exchange spending nearly 99 trillion rupiah per year due to the use of foreign fleets, and the creation of new jobs as a supporter of the maritime industry. So the presence of workers who have competence in the field of shipbuilding (ship building, naval architecture, marine engineering enginerring and maritime transportation) is urgently needed and their capability to compete with other countries that previously controlled the sea as a source of national income should be the Indonesian government's attention. Keywords: Professional shipbuilding techniques, competency